2002
DOI: 10.1063/1.1480886
|View full text |Cite
|
Sign up to set email alerts
|

AlGaInN-based ultraviolet light-emitting diodes grown on Si(111)

Abstract: Ultraviolet light-emitting diodes grown on Si(111) by gas-source molecular-beam epitaxy with ammonia are described. The layers are composed of superlattices of AlGaN/GaN and AlN/AlGaInN. The layers are doped n and p type with Si and Mg, respectively. Hole concentration of 4×1017 cm−3, with a mobility of 8 cm2/Vs, is measured in Al0.4Ga0.6N/GaN. We demonstrate effective n- and p-type doping of structures based on AlN/AlGaInN. Light-emitting diodes based on these structures show light emission between 290 and 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
65
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 20 publications
0
65
0
Order By: Relevance
“…1,2 However, up to now the research focus has primarily been GaN, ternary InGaN, AlGaN, and quaternary AlInGaN alloys with optical transitions in the 280-550 nm range. [3][4][5] Molecular beam epitaxy or metalorganic chemical vapor deposition ͑MOCVD͒ techniques were primarily used to grow the studied high-quality films and quantum structures on substrates such as sapphire, SiC, or bulk GaN. To push the optical emission/detection wavelength to the deep UV region (xр280 nm) high-quality Al x Ga 1Ϫx N alloys with Al-mole fractions in excess of x ϭ0.5 are needed.…”
mentioning
confidence: 99%
“…1,2 However, up to now the research focus has primarily been GaN, ternary InGaN, AlGaN, and quaternary AlInGaN alloys with optical transitions in the 280-550 nm range. [3][4][5] Molecular beam epitaxy or metalorganic chemical vapor deposition ͑MOCVD͒ techniques were primarily used to grow the studied high-quality films and quantum structures on substrates such as sapphire, SiC, or bulk GaN. To push the optical emission/detection wavelength to the deep UV region (xр280 nm) high-quality Al x Ga 1Ϫx N alloys with Al-mole fractions in excess of x ϭ0.5 are needed.…”
mentioning
confidence: 99%
“…In the active region of the device, consisting of five undoped barrier/well pairs and placed between n-and p-regions, the well thickness was increased to 0.75 nm to increase the electroluminescence efficiency [5]. These thicknesses are below the critical layer thickness [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work has shown that diodes based on superlattices (SLs) of AlN/AlGaInN can be used to produce both LEDs with light emission down to 280 nm [5] and photodetectors with sensitivity edge near 260 nm [9]. This is accomplished using SLs of AlN and AlGaInN with extremely small well and barrier thicknesses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] For such devices, AlGaN is the most suitable material where the emission wavelength can be tuned from 365 to 200 nm as the Al content increases. However, to realize high-efficiency DUV-LEDs, several challenges are still awaiting for us.…”
Section: Introductionmentioning
confidence: 99%